Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-155
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic transfer: A comparison study of F0 patterns in L2 English by Chinese speakers

Abstract: A comparison was made among the fundamental frequency (F0) patterns of continuous speech in English, Mandarin Chinese and L2 English produced by Chinese speakers. Ten adult native Chinese speakers were asked to read narrative text written in both English and Chinese. The comparative analysis of 300 sentences was performed in the following aspects: F0 mean, pitch range, pitch change rate and pitch change amount. It is found that in terms of both pitch range on the phoneme level and pitch change amount on the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Pitch characteristics of L2 speech have also been studied in the literature. It is generally agreed that the pitch form of L2 differs to some degree from what is considered the native norm [6][7][8][9][10][11]. Some studies have found a compressed pitch range and less pitch variation in L2 speech [6,8], which might be attributed to less confidence in L2 production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitch characteristics of L2 speech have also been studied in the literature. It is generally agreed that the pitch form of L2 differs to some degree from what is considered the native norm [6][7][8][9][10][11]. Some studies have found a compressed pitch range and less pitch variation in L2 speech [6,8], which might be attributed to less confidence in L2 production.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the influence/transfer of L1 prosody is also apparent in L2 speech. [10] reported that in terms of both pitch range on the phoneme level and pitch change amount on the utterance level, L2 English speech by Chinese speakers displayed a larger value than L1 English. [7] reported that the pitch range of content words is larger in L2 English speech by Japanese speakers than in L1 English.…”
Section: Introductionmentioning
confidence: 99%
“…But these metrics were only extracted from the acoustic signal, without reference to any phonetic information. In a recent study by Ding et al (2016), a comparison was made among the fundamental frequency (F0) patterns of continuous speech in English, Mandarin Chinese and L2 English produced by Chinese speakers. Ten adult native Chinese speakers were asked to read narrative text written in both English and Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem is that Chinese speakers can hardly pronounce English letters as the natives do. Mandarin Chinese speakers usually pronounce English words with a certain Chinese accent [8]. When English letters are combined with Chinese characters, speakers even try to adjust the pronunciation of the letters to fit the Chinese phonological systems.…”
Section: Introductionmentioning
confidence: 99%